Competent and competent application of Kazakh in the press (Herald of Journalism, 2018)
Authors of article analyze language and style of modern Kazakh journalism. Also the structure, methodology and content of texts of creative works in Kazakh is investigated. Rassmatrena language features and uniqueness of style of works of writers and publicists. According to authors the text of the literary and publicistic work has to be unique, original, substantial, clear, clear, and also may contain specific receptions and the author’s methods. Authors note that style of the writer is exclusive and his difference from other style consists in the importance of thematic sense, depth of development of contents, originality of creative receptions, perfection of a form of the work.